Which laboratory tests are chosen by physicians for the diagnosis and follow-up of rheumatic diseases? [Hekimler romatizmal hastaliklarin tani ve takibinde hangi laboratuvar testlerini seçiyorlar?] - (:unkn) unknown (My University, 2007)
Objective: Laboratory tests are widely used for the diagnosis and follow-up of rheumatic diseases. Most of these are not specific, but used to support me diagnosis. The aim of this study was to define laboratory tests that are used to diagnose rheumatic disorders by physicians in physical medicine and rehabilitation (PMR), internal medicine/ rheumatology department. Materials and Methods: A total of 138 physicians both resident and specialist from PMR (73.9%) and internal medicine (26.1%) departments participated into the study. The physicians were asked which laboratory tests they mostly used for the diagnosis and follow up of osteoarthritis, rheumatoid arthritis, ankylosing spondylitis and fibromyalgia syndrome. Results: We found that erythrocyte sedimentation rate (ESR) and Creactive protein (CRP) were mostly used for the diagnosis of these diseases (p<0.05). In addition, 97.7% of physicians chose to know rheumatoid factor for the diagnosis of rheumatoid arthritis. Residents needed more laboratory tests to diagnose osteoarthritis and fibromyalgia syndrome when compared to specialists (p<0.001). Conclusion: While the laboratory tests were ordered in the assessment of a rheumatic disease, physicians should consider if these tests provide optimal benefit and contribution for the diagnosis and follow-up of the diseases. However, physicians should avoid ordering unnecessary tests for diagnosis and follow-up of the rheumatic disease. Copyright © 2007 by Türk Tibbi Rehabilitasyon Kurumu Derneǧi.
Keywords: Ankilosing spondylitis; Fibromyalgia; Laboratory tests; Osteoarthritis; Rheumatoid arthritis and rheumatic diseases